The Moderating Effect of Institutional Shareholders on the Relationship between Board Attributes and Auditor Selection among Listed Financial Service Firms in Nigeria - Musa, Haruna Muhammed (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The study examines the moderating effect of institutional ownership on the relationship between board attributes and auditor selection among listed financial service firms in Nigeria. It investigated whether institutional shareholding moderate the relationship between board size, board independence, board gender diversity, board meeting attendance and auditor selection among listed financial firms in Nigeria. The study used secondary data extracted from the published financial statements of the sampled firms for the period 2007 to 2020. The population of the study consists of 53 listed financial service firms in Nigeria. The study adopts correlational research design using logistic regression as a tool of analysis. This study presents evidence that higher levels of institutional ownership strengthen the effect of board attributes (gender diversity and board meeting attendance) on auditor selection. Hence, the result implies that managers may face stringent monitoring when institutional investors, board gender diversity and board meeting attendance interacts. Such superior monitoring may compel managers to consider hiring an industry specialist auditor to audit the firm which leads to boosting the firm’ value. The finding of this investigation has an important policy implication on enhancing sound corporate governance practices, particularly for firms operating in developing countries where the market for corporate control is ineffective.